Macromedia flash бағдарламасымен жұмыс жасау және оның мүмкіндіктері - Пердебаева, Ұ.Б. (My University, 2013)
Work with program Macromedia flash is very convenient. There is a possibility of creation of electronic textbooks, electronic greetings, developing illustration and creation of Web pages.